Treatment outcomes in patients with laryngotracheal lesions and compromised airway during and prior to the coronovirus disease 2019 pandemic: a tertiary institution's experience. Issue 10 (13th October 2021) - Gombert, E; Ishii, A; Guilcher, P; Gorostidi, F; Cantarella, G; Pignataro, L; Sandu, K
Abstract: Objective: This study aimed to compare treatment outcomes in patients with laryngeal and tracheal stenosis treated during and prior to the coronavirus disease 2019 pandemic period. Method: Patients treated for laryngotracheal lesions with impending airway compromise during the active pandemic period were matched with those treated for similar lesions in the preceding years in a monocentric tertiary hospital setting. Results: During the pandemic period of 55 days, 31 patients underwent 47 procedures. Seven patients (2 children, 5 adults) had open airway surgery, and one had an operation-specific complication. Twenty-four patients (10 children, 14 adults) underwent 40 endoscopic interventions without any complications. Operation specific results during and prior to the pandemic were comparable. Conclusion: The management strategy in patients with laryngotracheal lesions and impending airway compromise should not be altered during periods of risk from coronavirus disease 2019. Avoiding a tracheostomy by performing primary corrective surgery or proceeding with a definitive decannulation would be beneficial in these patients to reduce the risk of contagion.